Analysis of Access to Credit Facilities to Small-Scale Farmers in Wukari Local Government Area of Taraba State, Nigeria - A, Olayiwola S.; B, Magaji S. (Darul Yasin Al Sys, 2024)
This study analyzed factors affecting access to credit facilities of small-scale farmers in Wukari Local Government area of Taraba State, Nigeria. A multistage sampling technique was used to collect primary data from 120 respondents using a structured questionnaire. Data collected was analyzed using descriptive statistics and binary logistic regression. Result revealed that, 59.2% of the respondents were male, average age was 34years and 43.3% of the respondents were married. The result also revealed that average household size was about 6 while 60.8% of the respondents acquired tertiary education. Majority (72.5%) of the respondents had access to credit and most (60.8%) sourced their loan through informal institution. Respondents (53.3%) agreed that there was misappropriation of credit and the reason for misappropriation was low yield of the farm outputs. The binary logistic regression revealed that educational level, annual farm income, farm size, membership of cooperative and age were significantly affected access to credit in the study area. The major constraints faced small-scale farmers in the study area were high interest rate (3.37), lack of collateral (3.28), low amount of loan (3.19) as well as delay in approval and disbursement (3.10). This study provides critical insights into the dynamics of credit access among small-scale farmers, offering a foundation for policy interventions and future research aimed at improving the financial inclusivity and economic resilience of this vital sector.